RETRACTED: Ensuring food safety using digital technologies - Cherkasova Elmira; Golinitsky Pavel; Antonova Uliana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001